The Concept of Property and Ownership in Islam - Abdurrahman Siregar (Randwick International of Social Science Journal, 2021)
The aim of this research is to know how the concept of property ownership in Islamic economics according to Afzalur Rahman, to know how to implement the concept of property ownership in Islamic economics by Afzalur Rahman at this time and to know how Afzalur Rahman's thought analysis of concepts ownership of property in Islamic economics. The research method that writer use is library research (library research) where the data and data sources are obtained from a review of the literature according to the problem. The result showed that the opinion expressed by Afzalur Rahman on the concept of ownership in the Islamic economic system is in harmony with the economic principles that require the system an economy compatible with the Qur'an and Sunnah. Where Islam also wants every person in possession of good property in the form of goods or services obtained in a way halal both the form of substance and how to get it, not destroy and destroy human nature, nor do the persecution and exploitation, the purpose ultimately is to fight for the needs of human life and seek pleasure Hereafter is blessed by Allah SWT.